Principal Component Analysis to Determine the Main Factors of Stock Prices - Shabrina Luthfiah Destiyana; Andrieta Shintia Dewi (Budapest International Research and Critics University, 2022)
Stock investments reach the point of maximum profit when good observations are made. The many variables that determine stock prices make it difficult for potential investors to identify which stocks are the right ones to invest in. So, it is necessary to reduce the variables to form the main component without eliminating the information that existed before. This study aims to determine what variables are forming the main factors in determining stock prices in the Consumer Non-Cyclicals sector companies indexed by LQ45 using 18 independent variables and stock prices as the dependent variable. This study uses the Principal Component Analysis method to form a new component that determines stock prices, which is called the principal component. The results showed that the main factor determining the stock price of companies coded as CPIN issuers, namely forming 3 components, in HMSP which formed 5 components, in GGRM which formed 5 components, in JPFA namely forming 5 components, in UNVR which formed 5 components, in INDF which formed 5 components, and the company coded the ICBP issuer, which formed 4 components.